Efficacy of Prednisolone for Bell Palsy in Children: A Randomized, Double-Blind, Placebo-Controlled, Multicenter Trial. (15th November 2022) - Babl, Franz E.; Herd, David; Borland, Meredith L.; Kochar, Amit; Lawton, Ben; Hort, Jason; West, Adam; George, Shane; Zhang, Michael; Velusamy, Karthik; Sullivan, Frank; Oakley, Ed; et al.
Abstract : Background and Objectives: Corticosteroids are used to treat the early stages of idiopathic facial paralysis (Bell palsy) in children, but their effectiveness is uncertain. We set out to determine whether prednisolone improves the proportion of children with Bell palsy with complete recovery at 1 month. Methods: We conducted a double-blind, placebo-controlled, randomized trial of prednisolone in children presenting to emergency departments with Bell palsy. Patients aged 6 months to younger than 18 years were recruited within 72 hours after the symptom onset and were randomly assigned to receive 10 days of treatment with oral prednisolone (approximately 1 mg/kg) or placebo. The primary outcome was complete recovery of facial function at 1 month rated on the House-Brackmann scale. Secondary outcomes included facial function, adverse events, and pain up to 6 months. Target recruitment was n = 540 (270 per group). Results: Between October 13, 2015, and August 23, 2020, 187 children were randomized (94 to prednisolone and 93 to placebo) and included in the intention-to-treat analysis. At 1 month, the proportions of patients who had recovered facial function were 49% (n = 43/87) in the prednisolone group compared with 57% (n = 50/87) in the placebo group (risk difference −8.1%, 95% CI −22.8 to 6.7; adjusted odds ratio [aOR] 0.7, 95% CI 0.4 to 1.3). At 3 months, these proportions were 90% (n = 71/79) for the prednisolone group vs 85% (n = 72/85) for the placebo group (risk difference 5.2%, 95% CI −5.0 to 15.3; aOR 1.2, 95% CI 0.4 to 3.0) and, at 6 months, 99% (n = 77/78) and 93% (n = 76/82), respectively (risk difference 6.0%, 95% CI −0.1 to 12.2; aOR 3.0, 95% CI 0.5 to 17.7). There were no serious adverse events and little evidence for group differences in secondary outcomes. Discussion: In children with Bell palsy, the vast majority recover without treatment. This study, although underpowered, does not provide evidence that early treatment with prednisolone improves complete recovery. Trial Registration Information: Registered with the Australian New Zealand Clinical Trials Registry ACTRN12615000563561, registered June 1, 2015. anzctr.org.au/Trial/Registration/TrialReview.aspx?id=368505&isReview=true . Classification of Evidence: This study provides Class I evidence that for children with Bell palsy, prednisolone does not significantly change recovery of complete facial function at 1 month. However, this study lacked the precision to exclude an important harm or benefit from prednisolone.